2018
DOI: 10.1111/mec.14914
|View full text |Cite
|
Sign up to set email alerts
|

Two key features influencing community assembly processes at regional scale: Initial state and degree of change in environmental conditions

Abstract: Belowground microbial communities strongly influence ecosystem function such that predicting function may rely on understanding ecological processes that assemble communities. Uncertainty remains, however, in what governs the relative contributions of different ecological processes. To help fill this knowledge gap, we test the general hypothesis that both initial state and degree of change in environmental conditions govern the relative contributions of different ecological assembly processes. To do so, we lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(112 citation statements)
references
References 57 publications
4
100
1
Order By: Relevance
“…For example, bacterial community assembly processes and composition shift in response to increases in SOC due to organic manure application in many agroecosystems (Feng et al, 2015, 2017). The importance of SOC on microbial assembly processes and agricultural sustainability had been observed in previous investigations of upland and paddy soils (Dini‐Andreote et al, 2015; Feng, Chen, et al, 2018), and our work suggests that this relationship could be a general feature of all agroecosystems.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…For example, bacterial community assembly processes and composition shift in response to increases in SOC due to organic manure application in many agroecosystems (Feng et al, 2015, 2017). The importance of SOC on microbial assembly processes and agricultural sustainability had been observed in previous investigations of upland and paddy soils (Dini‐Andreote et al, 2015; Feng, Chen, et al, 2018), and our work suggests that this relationship could be a general feature of all agroecosystems.…”
Section: Discussionsupporting
confidence: 83%
“…Recent work of Tripathi et al (2018) and Sengupta et al (2019) has supported this assumption: stochasticity was dominant under mild environmental conditions, whereas determinism contributed a greater proportion of assembly processes under extreme conditions. Flooding can also promote soil fertility in rice paddies and lead to higher resource bioavailability that releases micro‐organisms from environmental stresses (Chen, Zhang, & Effland, 2011; Feng, Chen, et al, 2018; Feng et al, 2017). Collectively, these ecosystem features are likely to enhance stochastic processes relative to determinism.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental filtering is a key determinant of community assembly (Kraft et al ., ) and has been shown to cause phylogenetic clustering in bacterial communities (Horner‐Devine and Bohannan, ). Many studies have shown that soil pH, OMs and salinity can influence bacterial community assembly processes in various environments (Dini‐Andreote et al ., ; Feng et al ., ; Tripathi et al ., ; Zhang et al ., ). Here, we showed that soil pH and MAT mediated the balance between stochastic and deterministic assembly for abundant and rare sub‐communities, respectively, in agro‐ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…To advance mechanistic understanding of community assembly processes, the factors that mediate the balance between stochastic and deterministic processes must be elucidated (Feng et al ., ). A study showed that soil pH influences the balance between stochastic and deterministic processes in shaping soil bacterial community assembly during the paedogenic processes (Tripathi et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation